Applications of cerebrospinal fluid circulating tumor DNA in the diagnosis of gliomas. (10th February 2020) - Zhao, Zhenyu; Zhang, Cheng; Li, Mi; Shen, Yiping; Feng, Shiyu; Liu, Jialin; Li, Fangye; Hou, Lei; Chen, Zhong; Jiang, Jingjing; Ma, Xiaodong; Chen, Ling; et al.
Abstract: Objective: The 2016 World Health Organization (WHO) Classification of Tumors of the Central Nervous System (CNS) was revised to include molecular biomarkers as diagnostic criteria. However, conventional biopsies of gliomas were spatially and temporally limited. This study aimed to determine whether circulating tumor DNA (ctDNA) from cerebrospinal fluid (CSF) could provide more comprehensive diagnostic information to gliomas. Methods: Combined with clinical data, we analyzed gene alterations from CSF and tumor tissues of newly diagnosed patients, and detected mutations of ctDNA in recurrent patients. We simultaneously analyzed mutations of ctDNA in different glioma subtypes, and in lower-grade gliomas (LrGG) versus glioblastoma multiforme (GBM). Results: CSF ctDNA mutations had high concordance rates with tumor DNA (tDNA). CSF ctDNA mutations of PTEN and TP53 were commonly detected in recurrent gliomas patients. IDH mutation was detected in most of CSF ctDNA derived from IDH -mutant diffuse astrocytomas, while CSF ctDNA mutations of RB1 and EGFR were found in IDH -wild-type GBM. IDH mutation was detected in LrGG, whereas Rb1 mutation was more commonly detected in GBM. Conclusions: CSF ctDNA detection can be an alternative method as liquid biopsy in gliomas. Abstract : CtDNA from CSF could provide supplementary diagnostic information on gliomas.